The conference on the future of Europe: the future of legal Europe : will we trust in it? - Müller-Graff, Peter-Christian (ERA-Forum, 2021)
The agenda of the Conference on the Future of Europe contains the potential for numerous legislative recommendations. This raises the question of the future resilience of Union law. The article, which is based on the author’s introductory speech of ERA’s webinar on the Conference, assesses the challenges and chances of the Union’s capacity to engage in proper rule-making, to experience compliant rule-implementation and to beneﬁt from a judiciary which reliably settles disputes. It concludes that as long as the demanding requirements of an enlightened legal civilisation are fulﬁlled there is no reason not to trust in Legal Europe’s future.